A recently discovered species of Apiomorpha Rübsaamen (Hemiptera: Coccoidea: Eriococcidae) with unusual gall morphology - Mills, Penelope J.; Macdonald, Melanie L.; Rigby, Lisa M.; Cook, Lyn G. (Zootaxa, 2011)
Australia has a diverse array of gall-inducing scale insects (Hemiptera: Sternorrhyncha: Coccoidea), most of which feed on eucalypts. Here we describe a recently discovered and previously unrecognised species of Apiomorpha Rübsaamen that induces an unusual gall. Galls of the adult females were first found in bushland in South West Rocks, in northern New South Wales (Australia), but the original location has been cleared for housing development. Additional specimens have been discovered in nearby bushland and near the Arakoon Conservation Park, NSW. All specimens observed to date occur on Eucalyptus racemosa Cav. The morphology of the adult female and COII mtDNA sequences suggest affinities with the Apiomorpha minor (Froggatt) species-group of Gullan (1984), but the gall of the adult female is quite distinct from those of other members of that species-group in that it has two chambers instead of one. In addition, the newly recognised species, A. nookara Mills, MacDonald, Rigby & Cook sp. n., has a diploid chromosome complement of 2n = 6, a count not yet noted for members of the A. minor species-group. The description of the species was partly prepared by undergraduates at The University of Queensland, who were helping to overcome the so-called "taxonomic impediment" by describing and naming previously undescribed taxa.